UPAYA PENINGKATAN PRESTASI BELAJAR IPS MELALUI PENDEKATAN LEARNING COMMUNITY DI SMP NEGERI 2, BANDA ACEH - . Ernita (Jurnal Pencerahan, 2015)
In the process of learning, is often found a tendency to minimize the participation of students in the class. The dominance of the teacher in the learning process leads to the tendency of students become more passive. In the implementation, assessing the learning process of the subject of Social Sciences is boredom because of its monotonous and expository presentation so that students are less enthusiastic, resulting of less interesting in the subjects. Having observed this classroom situation, it is necessary to think about ways of presenting and learning atmospheres. The suitable learning process of social sciences subject for students is that the learning community based model. This learning focuses on the processes and interactions in the social context. Interaction and social process should be a concern in achieving the learning objectives.Learning community based model is a concept of the creation of learning communities in schools, the learning process between teachers and teachers, teachers and students, students with students, and even among the school communities with the community outside the school, so that the student achievement can be improved. This design of this study was based on the classroom action research at the Junior High School, SMP Negeri 2 Banda Aceh. The study found that the learning community based model has improved student learning outcomes in both first and the second cycles. Thus, the learning community based model was found to be a suitable way of improving students’ achievement in learning the subject of social sciences at the SMP Negeri 2, Banda Aceh.